2022
DOI: 10.3390/vetsci9080384
|View full text |Cite
|
Sign up to set email alerts
|

Human and Animal Brucellosis in Nigeria: A Systemic Review and Meta-Analysis in the Last Twenty-One Years (2001–2021)

Abstract: The global burden of human and animal brucellosis remains enormous. The disease, which is endemic in Nigeria, lacks appropriate attention and national data. This review estimated the burden and distribution of human and animal brucellosis in Nigeria in the last twenty years (2001–2021). Publications reporting the detection of brucellosis in Nigeria were sorted from different search engines, including PubMed, ResearchGate, Scopus, and Google Scholar, to generate data on its prevalence, spatial distribution, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 96 publications
0
10
2
Order By: Relevance
“…The similarity in animal-level seroprevalence results between countries within the East African region could be attributed to similarities in traditional grazing practices as most regions from which studies have been conducted happen to be in pastoral areas, where different animal species are mixed, and grazing pastures and watering points are shared. Globally, the prevalence detected in this study was lower than for Nigeria, Ethiopia, and Angola, respectively ( Mufinda et al , 2015 ; Ogugua et al , 2018 ; Akinyemi et al , 2021 ; Tschopp et al , 2021 ). The variations in results observed in different studies may probably be attributed to several factors such as the epidemiological situation, sampling techniques, sample sizes, different diagnostic tests used, and interpretations of results.…”
Section: Discussioncontrasting
confidence: 71%
“…The similarity in animal-level seroprevalence results between countries within the East African region could be attributed to similarities in traditional grazing practices as most regions from which studies have been conducted happen to be in pastoral areas, where different animal species are mixed, and grazing pastures and watering points are shared. Globally, the prevalence detected in this study was lower than for Nigeria, Ethiopia, and Angola, respectively ( Mufinda et al , 2015 ; Ogugua et al , 2018 ; Akinyemi et al , 2021 ; Tschopp et al , 2021 ). The variations in results observed in different studies may probably be attributed to several factors such as the epidemiological situation, sampling techniques, sample sizes, different diagnostic tests used, and interpretations of results.…”
Section: Discussioncontrasting
confidence: 71%
“…Brucellosis is regarded as one of the most lethal zoonotic diseases that affects both animals and humans. It is caused by the Brucella species with widely varying prevalence from one country to another both in animals and humans [ 42 , 45 ]. People working in the livestock industry are considered to be at risk of contracting Brucellosis because of its occupational hazards.…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, brucellosis is usually considered an occupational health hazard that mainly affects livestock handlers such as butchers, farmers, laboratory staff, slaughter workers, and veterinarians [ 39 , 40 , 41 ]. The disease is also known as the travel-related infectious disease “gastric remittent fever”, “Malta fever”, “Mediterranean fever”, or “undulant fever” [ 42 ]. Brucellosis has been substantially eradicated in many industrialized countries, including New Zealand, Australia, Canada, Japan and some member countries of the European Union (Denmark, Belgium, Germany, Finland, Ireland, Luxembourg, Sweden, The Netherlands, the United Kingdom).…”
Section: Introductionmentioning
confidence: 99%
“…Human brucellosis is endemic in Nigeria, where it lacks appropriate attention and national data. A systematic review showed that the national seroprevalence of human brucellosis was 17.6% (554/3,144) from 2001 to 2021, and the peak was observed in 2016 in southeastern Nigeria [ 62 ].…”
Section: Africamentioning
confidence: 99%